On one class of quaternionic mappings - Kuz’menko, T. S.; Shpakovskii, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We consider a new class of quaternionic mappings associated with spatial partial differential equations. We obtain a description of all mappings from this class by using four analytic functions of complex variable.